Effects of simulated acid rain on morphological traits of Thai rice cultivars - Jakkrit Sreesaeng,; Phanuphong Kongchiu,; Sutkhet Nakasathien, (Agriculture and Natural Resources, 2021)
Increasing air pollution is associated with acid precipitation (especially acid rain and acid fog), a serious environmental issue that affects plant growth and development. This study investigated the effects of simulated acid rain (pH adjusted to 2.5, 3.5, 4.5, 5.5 and 6.5 as a control using 5:1 volume per volume mix of H2SO4 and HNO3) on the growth and development of 10 rice cultivars during the vegetative growth stage under greenhouse conditions. The results showed that simulated acid rain at pH 2.5–3.5 reduced the chlorophyll (SPAD) index values at both 4 and 8 d after spraying. However, increasing the acidity of the simulated acid rain promoted the plant height, number of leaves and root-to-shoot ratio compared with the control, indicating that simulated acid rain promoted rather than inhibited some characteristics of rice. Simulated acid rain at pH 2.5 produced white-to-tan spots on the abaxial surfaces of the rice leaves, with the frequency of these necrotic spots depending on the rice cultivar. The visual scoring effects of simulated acid rain at pH 2.5 revealed that CMJ, KDML105, TTCP and HPYTD were moderately affected cultivars, RD27 and KTH17 were tolerant cultivars and RD57, RD31, MLL and KKN were highly tolerant cultivars.The results indicated that rice is moderately tolerant to simulated acid rain.